Case Report: BAP1 Mutation and RAD21 Amplification as Predictive Biomarkers to PARP Inhibitor in Metastatic Intrahepatic Cholangiocarcinoma - Sabbatino, Francesco; Liguori, Luigi; Malapelle, Umberto; Schiavi, Francesca; Tortora, Vincenzo; Conti, Valeria; Filippelli, Amelia; Tortora, Giampaolo; Ferrone, Cristina R.; Pepe, Stefano (Frontiers in Oncology, 2020)
Introduction: Intrahepatic cholangiocarcinoma (ICC) is a rare hepatobiliary cancer characterized by a poor prognosis and a limited response to conventional therapies. Currently chemotherapy is the only therapeutic option for patients with Stage IV ICC. Due to the poor response rate, there is an urgent need to identify novel molecular targets to develop novel effective therapies. Precision oncology tests utilizing targeted next-generation sequencing (NGS) platforms have rapidly entered into clinical practice. Profiling the genome and transcriptome of cancer to identify potentially targetable oncogenic pathways may guide the clinical care of the patient. Case presentation: We present a 56-year-old male patient affected with metastatic ICC, whose cancer underwent several precision oncology tests by different NGS platforms. A novel BAP1 mutation (splice site c.581-17_585del22) and a RAD21 amplification were identified by a commercial available platform on a metastatic lesion. No germline BAP1 mutations were identified. Several lines of evidences indicate that PARP inhibitor administration might be an effective treatment in presence of BAP1 and/or RAD21 alterations since both BAP1 and RAD21 are involved in the DNA repair pathway, BAP1 interacts with BRCA1 and BRCA1-mediated DNA repair pathway alterations enhance the sensitivity to PARP inhibitor administration. In this case, after failing conventional therapies, patient was treated with PARP inhibitor olaparib. The patient had a partial response according to RECIST criteria with an overall survival of 37.2 months from the time of diagnosis of his ICC. Following 11.0 months on olaparib treatment, sustained stable disease control is ongoing. The patient is still being treated with olaparib and no significant toxicity has been reported. Conclusion: These findings have clinical relevance since we have shown PARP inhibitor as a potential treatment for ICC patients harboring BAP1 deletion and RAD21 amplification. We have also highlighted the utility of NGS platforms to identify targetable mutations within a cancer.